Entre a mulher ideal e a mulher moderna: representações femininas na imprensa mineira - 1873-1932 - Kelly Cristina Nascimento (2006)
The present paper has as main subject to analyze some questions on the feminine emancipation by means of the womans representations presented by the press between 1873 and 1932, including diverse cities of Minas Gerais. For this work, the press is understood as a convenient source for the analysis, since through the periodicals analysis it could be evaluated how some society sections faced the feminine behavior and created representations for the women. Therefore emphasis was given to three main thematics in order to understand the speech which was passed on: the education, social behavior and feminine suffrage. In a general way, it was observed that the woman from Minas Gerais was represented by the press having followed some norms considered as ideal ones by the scientific theories, religious speeches and social conveniences dictated by the elites of Minas Gerais.